Creating a national federation of archives using OAI-PMH - Ferros, Luís (2008)
This paper describes the planning stages of the creation of a national level federation of archives. The Open Archives Initiative Protocol for Metadata Harvesting will be used for collecting metadata being produced by local archives using any compliant records management software. The first stage of implementation will harvest metadata produced with the DigitArq [1-3] platform in a pilot group of Portuguese Regional Archives. DigitArq relies on Encoded Archival Description (EAD) metadata to describe its collections. However, the overwhelming flexibility and complexity of EAD make the harvesting operation more complex than usual. This paper addresses possible ways of exchanging EAD records using OAI-PMH as the basis for a central repository of metadata that will enable the creation of advanced information services at the national level.